Los materiales del castro de San L.Luis (Allande, Asturias) - Marín Suárez, Carlos (Complutum, 2007)
The purpose of this paper is to show to the scientific community the ceramic materials, in the main unpublished, obtained during the archaeological excavations of the sixties at the “low neighborhood” of the San L.luis’s hillfort (Allande, Asturias, North of Spain). These materials indicate unequivocally the existence of levels of the second Iron Age. Also we propose a theoretical reflection on the study of the ceramic technology, thanks to the application of anthropologic concepts, applying the Technologicall Operative Chains (TOC) and overcoming definitively the typologics analyses. All that allows us to present the ceramic basic types and technologies from the IVth century B.C. in the western of Asturias. The union of the TOC and of the contextual analyses allows to raise hypothesis of social processes, which in our concrete case of study we present in key of gender.